The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/v14030643
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Genetics and Evolutionary Properties of Eurasian Avian-like H1N1 Swine Influenza Viruses in Liaoning

Abstract: Swine influenza virus (SIV) is an important zoonosis pathogen. The 2009 pandemic of H1N1 influenza A virus (2009/H1N1) highlighted the importance of the role of pigs as intermediate hosts. Liaoning province, located in northeastern China, has become one of the largest pig-farming areas since 2016. However, the epidemiology and evolutionary properties of SIVs in Liaoning are largely unknown. We performed systematic epidemiological and genetic dynamics surveillance of SIVs in Liaoning province during 2020. In to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
5
2
Order By: Relevance
“…( 4 ) and the G2 viruses reported by H. Li et al. ( 32 ). To evaluate the replication of these two viruses in mammals, groups of three BALB/c mice were intranasally (i.n.)…”
Section: Resultsmentioning
confidence: 89%
“…( 4 ) and the G2 viruses reported by H. Li et al. ( 32 ). To evaluate the replication of these two viruses in mammals, groups of three BALB/c mice were intranasally (i.n.)…”
Section: Resultsmentioning
confidence: 89%
“…The G4 EA virus HA binds preferentially to alpha 2,6-linked sialic acid receptors and replicates efficiently in human airway epithelial cells [33]. Given the zoonotic potential of the ancestral G4 EA H1N1 virus 13 [34], the identification of this novel lineage in Cambodia is of particular importance, and highlights concerns surrounding inter-regional spread of swIAVs as a key driver in the emergence of new virus lineages. We also found multiple instances of CS H1 coupled with EA N1.…”
Section: Discussionmentioning
confidence: 99%
“…This novel EA H1N2 has a unique gene constellation comprised of a swine-origin G4 EA H1-HA, a N2-HA originating from human viruses and internal genes from TRIG viruses. In contrast, the ancestral G4 EA H1N1 virus that emerged from pigs in Henan, China in 2011 [33], contained EA virus H1 and N1 genes, human H1N1/pdm09-derived internal genes and a TRIG-derived NS gene, and has since spread to other parts of China including Jilin, Liaoning and Tianjin [34]. The G4 EA virus HA binds preferentially to alpha 2,6-linked sialic acid receptors and replicates efficiently in human airway epithelial cells [33].…”
Section: Discussionmentioning
confidence: 99%
“…So far, at least seven different serum subtypes of SIV have been found, and classical swine H1N1, avian-like H1N1, and humanoid H3N2 strains are widely prevalent in pigs. Serological epidemiological investigation of SI showed that the distribution and evolution of SIV in China is becoming increasingly complex [51]. The application of BNV is of great significance to block the transmission of swine influenza virus in China.…”
Section: Discussionmentioning
confidence: 99%